Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan Kecamatan Mlonggo, Kabupaten Jepara (Studi Nasabah PT. Bank Tabungan Pensiunan Nasional Syari’ah Tbk) - Yanto Yanto; Naila Sofiana (Jurnal Rekognisi Akuntansi, 2017)
In line with the development of the Indonesian economy in recent years and several sectors in the economy experiencing quite good growth, one of which is the fisheries and marine sector. The fishery sector is also one of the government's targets in an effort to increase non-oil and gas exports. With such great potential, the marine and fisheries sector can become a leading sector in the national economy. These abundant marine resources can potentially be utilized to improve the standard of living in the welfare of fishing communities.The method used in this research isresearch using a quantitative approach. The research subjects are fishermen who have been registered as customers of PT. Bank Tabungan Pensiunan Nasional. Tbk branch of Mlonggo District, Jepara Regency, as the unit being analyzed. The research sample was 50 fishermen using random sampling technique. To find out the factors that affect the income of fishermen in Mlonggo sub-district, simple linear regression analysis is used.The results of the research from the respondents can be concluded that the variables of working capital, work experience, long working hours are positive and significantly affect fishermen's income. While the age variable is not significant in influencing the income of fishermen